Trajectories of labour market marginalisation among young adults with newly diagnosed attention-deficit/hyperactivity disorder (ADHD). (22nd October 2021) - Helgesson, M.; Rahman, S.; Björkenstam, E.; Gustafsson, K.; Amin, R.; Taipale, H.; Tanskanen, A.; Ekselius, L.; Mittendorfer-Rutz, E.
Abstract: Aims: Labour market marginalisation (LMM), i.e. severe problems in finding and keeping a job, is common among young adults with attention-deficit/hyperactivity disorder (ADHD). This study aimed to disentangle the extent of LMM as well as the heterogeneity in patterns of LMM among young adults with ADHD and what characterises those belonging to these distinct trajectories of LMM. Methods: This population-based register study investigated all 6287 young adults, aged 22–29 years, who had their first primary or secondary diagnosis of ADHD in Sweden between 2006 and 2011. Group-based trajectory (GBT) models were used to estimate trajectories of LMM, conceptualised as both unemployment and work disability, 3 years before and 5 years after the year of an incident diagnosis of ADHD. Odds ratios (ORs) with 95% confidence intervals (CIs) for the association between individual characteristics and the trajectory groups of LMM were estimated by multinomial logistic regression. Results: Six distinct trajectories of LMM were found: 'increasing high' (21% belonged to this trajectory group) with high levels of LMM throughout the study period, 'rapidly increasing' (19%), 'moderately increasing' (21%), 'constant low' (12%) with low levels of LMM throughout the study period, 'moderately decreasing' (14%) and finally 'fluctuating' (13%), following a reversed u-shaped curve. Individuals with the following characteristics had an increased probability of belonging to trajectory groups of increasing LMM: low educational level (moderately increasing: OR: 1.4; CI: 1.2–1.8, rapidly increasing: OR: 1.7; CI: 1.3–2.1, increasing high: OR: 2.9; CI: 2.3–3.6), single parents (moderately increasing: OR: 1.6; CI: 1.1–2.4, rapidly increasing: OR: 2.0; CI: 1.3–3.0), those born outside the European Union/the Nordic countries (rapidly increasing: OR: 1.7; CI: 1.1–2.5, increasing high: OR: 2.1; CI: 1.4–3.1), persons living in small cities/villages (moderately increasing: OR: 2.4; CI: 1.9–3.0, rapidly increasing: OR: 2.1; CI: 1.6–2.7, increasing high: OR: 2.6; CI: 2.0–3.3) and those with comorbid mental disorders, most pronounced regarding schizophrenia/psychoses (rapidly increasing: OR: 6.7; CI: 2.9–19.5, increasing high: OR: 12.8; CI: 5.5–37.0), autism spectrum disorders (rapidly increasing: OR: 4.6; CI: 3.1–7.1, increasing high: OR: 9.6; CI: 6.5–14.6), anxiety/stress-related disorders (moderately increasing: OR: 1.3; CI: 1.1–1.7, rapidly increasing: OR: 2.0; CI: 1.6–2.5, increasing high: OR: 1.8; CI: 1.5–2.3) and depression/bipolar disorder (moderately increasing: OR: 1.3; CI: 1.0–1.6, rapidly increasing: OR: 1.7; CI: 1.4–2.2, increasing high: OR: 1.5; CI: 1.2–1.9). Conclusions: About 61% of young adults were characterised by increasing LMM after a diagnosis of ADHD. To avoid marginalisation, attention should especially be given to young adults diagnosed with ADHD with a low educational level, that are single parents and who are living outside big cities. Also, young adults with comorbid mental disorders should be monitored for LMM early in working life.